A synthetic peptide derived from the tumor-associated protein mdm2 can stimulate autoreactive, high avidity cytotoxic T lymphocytes that recognize naturally processed protein. - Dahl, A; Beverley, P; Stauss, H (1996)
Studies in melanoma patients have shown that unaltered self proteins can function as targets for tumor-reactive CTL. Here, we have investigated in a murine model whether autoreactive CTL can be found against the widely expressed proteins cyclin D1, mdm2, and p53, which are frequently overexpressed in transformed cells. Sixteen MHC class I binding peptides were identified in these proteins, and seven of them consistently stimulated primary CTL in vitro. Avidity measurements revealed that the avidity of peptide-induced CTL differed by >1000-fold. The highest avidity CTL were induced by a peptide derived from mdm2. These CTL recognized target cells expressing mdm2 endogenously, while CTL generated against the remaining peptides were of lower avidity and did not recognize cells expressing relevant proteins endogenously. Generation of high avidity anti-mdm2 CTL required several cycles of peptide stimulation, suggesting that the CTL precursor frequency was low. The data show the normal T cell repertoire contains small numbers of potentially autoreactive CTL. Expansion of these CTL may lead to beneficial autoimmunity against tumors, but, equally, it may be the basis of detrimental autoimmune diseases.